Integrated Management of Character Education in Rural Elementary Schools: Implementation and Challenges - Arisman Arisman; Asmendri Asmendri; Yusuf Salam; Muhammad Fazis; Jamilus Jamilus (Journal of Education Research, 2026)
Character education in elementary schools frequently remains fragmented and ceremonial due to weak managerial coordination and insufficient continuous supervision. This study aims to analyze the management of character education in elementary schools by examining the integration of planning, implementation, and supervision functions in supporting students' character development. A qualitative descriptive approach was employed. Data were collected through semi-structured interviews, observations, and documentation involving principals, teachers, school staff, students, parents, and school committee members, then analyzed through data reduction, data display, and conclusion drawing. Findings indicate that character education management was implemented systematically through three interconnected functions: planning emphasized character-based program preparation with stakeholder involvement; implementation focused on collaboratively integrating character values into learning activities and school culture; and supervision was conducted continuously to ensure consistency in students' character formation. The study concludes that the effectiveness of character education depends on the integration of these three functions supported by effective school leadership, underscoring the importance of institutional management for sustainable character education.